Implementasi Kebijakan Penegasan Batas Daerah oleh Bagian Pemerintahan Sekretariat Daerah Kota Banjar - Anggun Mustika Septiana (Sekolah Tinggi Pembangunan Masyarakat Desa APMD, 2023)
This research is based on activities carried out in the Government Section of the Regional Secretariat of Banjar City which are related to the implementation of the Regional Boundary Affirmation policy between Banjar City and Ciamis Regency, West Java Province. In implementing the regional boundary confirmation policy carried out by the Government Section of the Banjar City Regional Secretariat, researchers found problems, including a lack of consistency in the implementation of Permendagri No. 59 of 2011 concerning the Regional Boundaries of Banjar City and Ciamis Regency, limited human resources, as well as limited facilities and infrastructure in the Government Section of the Regional Secretariat of Banjar City in implementing the regional boundary confirmation policy. This research uses qualitative research methods with a total of seven informants. The data collection techniques are carried out through observation, interviews, documentation and literature study. Meanwhile, data processing or analysis techniques are carried out in three stages, namely in the form of data reduction, data presentation and conclusions. Based on the research results, it was concluded that the implementation of the regional boundary confirmation policy between Banjar City and Ciamis Regency by the Government section of the Banjar City Regional Secretariat has gone well and is optimal as a whole. However, there are still several obstacles, including a lack of consistency in the implementation of regional boundary confirmation policies, the involvement of staff implementing regional boundary confirmation that has not run properly, and limited facilities and infrastructure for regional boundary confirmation.